On the applicability of Landsat TM images to Mediterranean forest inventories - Salvador, Raymond; Pons, Xavier (Forest Ecology and Management, 1998)
Landsat TM images were used in combination with field measurements to create models for Mediterranean forests. Radiometric data from those images were related to field data from a forest inventory by means of regression analysis. Trials using plots with radiometrically homogeneous surroundings were carried out to evaluate the effect of high spatial heterogeneity frequently found in Mediterranean forests. Simple regression models were found to be consistent with the expected radiometric response of vegetation, and most of the multiple regression models fitted the observations sufficiently in order to make quantitative predictions for field variables from the remote sensing images. According to this study, however, these models should be regarded as exploratory models rather than fully operational ones. Spatially and non-spatially related factors are suggested as causes of the remaining dispersion of models created.
Keywords: forest quantitative variables; predictive models; radiometric response; spatial heterogeneity